Associations of weight‐ or shape‐related bullying with diverse disordered eating behaviors in adolescents. Issue 9 (28th June 2021) - Day, Sinead; Bussey, Kay; Trompeter, Nora; Hay, Phillipa; Lonergan, Alexandra; Mitchison, Deborah
Abstract: Objective: Little research has investigated variables affecting the relationship between weight‐ or shape‐related bullying (WSB) and specific forms of disordered eating in adolescence. This study aimed to examine the relationship between WSB and eating disorder behaviors in Australian adolescents, and whether this relationship was moderated by body image attitudes. Method: Data were used from the first wave of the EveryBODY study, a survey of body image concerns and eating disorders in a large representative sample of Australian adolescents ( N  = 573), aged 11–19 years. Participants completed an online survey with measures of WSB frequency, body image attitudes (drives for thinness, leanness, and muscularity), and disordered eating behaviors. Results: Results indicated that frequency of WSB was positively associated with purging and muscularity‐oriented behavior (MOB), but not dietary restriction, binge eating, or compulsive exercise. The relationship between WSB and MOB was moderated by drive for muscularity, such that victimization frequency was positively associated with MOB for those with high, but not low, desire to attain a muscular physique. Discussion: Findings indicate that WSB is positively associated with purging and MOB but not other eating disorder behaviors, and that drive for muscularity moderates its effect on some behaviors. Understanding these relationships will be important in implementing tailored interventions for adolescents based on screening for victimization experiences and specific body image attitudes.